2016
DOI: 10.1590/s1984-82502016000100010
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a new and economical stability indicating RP-HPLC method for cefixime trihydrate

Abstract: The present work describes the development of a new high performance liquid chromatographic (HPLC) method for the determination of Cefixime trihydrate under different stress conditons as specified by ICH. For the analysis, a Phenomenex (250 x 4.6 mm, 5 µm particle size) ODS column and a SPD 20 A UV detector at 289 nm was used. The selected mobile phase was 10 mM disodium hydrogen phosphate (with 0.5% TEA, pH adjusted to 6.3 with OPA) and methanol in the ratio of 75:25 (v/v) in isocratic mode at a flow rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recent and comparative literature studies have been described for assay of CFX such as HPTLC, [ 9,10 ] spectrophotometry, [ 11–14 ] RP‐HPLC, [ 15,16 ] HPLC–MS, [ 8 ] HPLC‐UV, [ 17 ] and electrocatalytic oxidation. [ 18 ] An LC–MS/MS technique has been reported that quantifies CFX in human plasma utilizing cefetamet as the internal standard.…”
Section: Introductionmentioning
confidence: 99%
“…Recent and comparative literature studies have been described for assay of CFX such as HPTLC, [ 9,10 ] spectrophotometry, [ 11–14 ] RP‐HPLC, [ 15,16 ] HPLC–MS, [ 8 ] HPLC‐UV, [ 17 ] and electrocatalytic oxidation. [ 18 ] An LC–MS/MS technique has been reported that quantifies CFX in human plasma utilizing cefetamet as the internal standard.…”
Section: Introductionmentioning
confidence: 99%